NTPDase and 5′-nucleotidase as inflammatory markers in cattle naturally infected by Eurytrema coelomaticum. (October 2016) - Fávero, Juscivete F.; Schwertz, Claiton I.; Doleski, Pedro H.; Leal, Daniela B.R.; Machado, Gustavo; Manzoni, Alessandra G.; da Silva, Ester S.; Gabriel, Mateus E.; Stedille, Fernanda A.; Christ, Ricardo; Stefani, Lenita M.; Mendes, Ricardo E.; et al.
Highlights: Eurytrematosis is a disease caused by Eurytrema coelomaticum in cattle. Ectonucleotidases has an important role in modulating the inflammatory response. Seric NTPDase shows high activity in E. coleomanticum infected cattle. NTPDase has anti-inflammatory action, since it controls the levels of nucleotide ATP, a pro-inflammatory molecule. NTPDase and 5′nucleotidase have important features related to the infection and tissue damaged caused by parasites. Abstract: The aim of this study was to evaluate seric NTPDase and 5′nucleotidase activities of cattle naturally infected by Eurytrema coelomanticum, as well as to correlate them to histopathological lesions in the pancreas and the degree of parasitism. Blood samples and pancreas of 51 bovines were collected on a slaughterhouse in Southern Brazil: 33 from cattle naturally infected by E. coelomanticum (the Group A), and 18 from uninfected animals (the Group B). Infected animals showed an average of 532 parasites per pancreas. In the pancreatic histology, ducts displayed hyperplasia, stenosis, proliferation of fibrous tissue, and interstitial inflammatory infiltration of lymphocytes. The serum from infected animals showed an increase in NTPDase activity when ATP was used as substrate (P < 0.001). For the ADP substrate, there was no difference between groups regarding NTPDase activity (P = 0.37), as well as 5′-nucleotidase activity (P = 0.27). Correlating NTPDase activity (ATP substrate) with the degree of histopathological lesions (rho = 0.66, P < 0.001) and the parasitic load on the pancreas (rho = 0.65, P < 0.001), a positive correlation was observed. Similar results were found between the degree of histopathological lesions and NTPDase activity (ADP substrate; rho = 0.29, P = 0.03), and 5′nucleotidase activity (rho = 0.35, P = 0.01). Based on the results of NTPDase and 5′nucleotidase enzymes in cattle naturally infected by E. coleomanticum, it is possible to suggest that these enzymes are involved in the modulation of inflammation, and they can act as markers of inflammatory response.